Case report: Psoriasiform eczema with immune-mediated comorbidities treated with upadacitinib - Salvi, Ilaria; Parodi, Aurora; Cozzani, Emanuele; Burlando, Martina (Frontiers in Immunology, 2024)
Immune-mediated comorbidities in patients with psoriasiform eczema are common. It can be challenging to manage multiple immune-mediated diseases, especially considering that biologic treatments are prone to causing paradoxical effects. The aim of this retrospective observational case series was to describe the course of both psoriasiform eczema and immune-mediated comorbidities in five patients treated with upadacitinib for psoriasiform dermatitis. Five patients, all male, were included. All the patients suffered from psoriasiform eczema. Moreover, two of the patients suffered from alopecia areata, two from vitiligo, one from ulcerative colitis and one from hidradenitis suppurativa. In all cases, the treatment with upadacitinib was rapidly effective on the eczema. The effectiveness on alopecia areata was good in both cases, while the results on vitiligo were only partial. The only case of ulcerative colitis achieved complete remission, while the case of hidradenitis suppurativa experience partial improvement. In conclusion, upadacitinib was effective in treating not only psoriasiform eczema, but also several immune mediated comorbidities. Additional studies are necessary to determine the efficacy of upadacitinib in alopecia areata, vitiligo and hidradenitis suppurativa.